2016
DOI: 10.1371/journal.ppat.1005678
|View full text |Cite|
|
Sign up to set email alerts
|

Bacillus anthracis Spore Surface Protein BclA Mediates Complement Factor H Binding to Spores and Promotes Spore Persistence

Abstract: Spores of Bacillus anthracis, the causative agent of anthrax, are known to persist in the host lungs for prolonged periods of time, however the underlying mechanism is poorly understood. In this study, we demonstrated that BclA, a major surface protein of B. anthracis spores, mediated direct binding of complement factor H (CFH) to spores. The surface bound CFH retained its regulatory cofactor activity resulting in C3 degradation and inhibition of downstream complement activation. By comparing results from wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 89 publications
1
26
0
Order By: Relevance
“…C1q is a component of human complement pathway which binds IgG, and apoptotic keratinocytes [78, 79]. BclA is implicated in a number of processes in B. anthracis infection including specific targeting to macrophages [80], and immunosuppressive activity via binding to complement factor H [81]. Notably, BclA does not appear to be directly involved in attachment as ΔbclA spores show no reduced binding to host cells but do exhibit a reduction in specific targeting to professional phagocytic cells [80].…”
Section: Discussionmentioning
confidence: 99%
“…C1q is a component of human complement pathway which binds IgG, and apoptotic keratinocytes [78, 79]. BclA is implicated in a number of processes in B. anthracis infection including specific targeting to macrophages [80], and immunosuppressive activity via binding to complement factor H [81]. Notably, BclA does not appear to be directly involved in attachment as ΔbclA spores show no reduced binding to host cells but do exhibit a reduction in specific targeting to professional phagocytic cells [80].…”
Section: Discussionmentioning
confidence: 99%
“…This BclA glycoprotein may have a role in spore protection (Boydston et al, 2005) and may play a role in host phagocytosis of the spore (Gu et al, 2012). It has recently been shown to mediate an immune inhibition mechanism that promotes spore persistence in mouse lung (Wang et al, 2016). ExsFA (also named BxpB) is a 17 kDa exosporium protein required for the efficient attachment of BclA to form the nap on the exosporium Sylvestre et al, 2005;Thompson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A32723). Dose-dependent C3b binding was analyzed by incubating bacteria with a concentration gradient (10,25,50, and 100%) of NHS (Merck). CRP and SAP binding on the bacterial surface was assessed using mouse anti-human CRP (Thermo Fisher, Cat.…”
Section: Flow Cytometry-based Binding Assaymentioning
confidence: 99%
“…These include the expression of cellular components and proteins on the pathogen surface that inhibit complement activation (18), blocking, or destabilization of the C3 convertase (19,20); recruitment of host complement regulatory proteins on the pathogen surface (21,22); and complement degradation by host plasminogen (23,24). Previous reports have suggested that the B. anthracis spore coat protein BclA has the propensity to bind with complement factor H (FH) and human serum plasminogen (24,25), which leads to C3 breakdown and imparts anti-opsonic properties to the spore. Considering the common characteristics of complement evasion and a higher survival rate exhibited by encapsulated bacteria compared with their non-encapsulated counterparts, it is conceivable that the B. anthracis PGA capsule may also exhibit complement antagonistic properties (11).…”
Section: Introductionmentioning
confidence: 99%